A tractable model of buffer stock saving - Christopher D. Carroll; Patrick Toche (Goethe University Frankfurt, Center for Financial Studies (CFS), 2009)
We present a tractable model of the effects of nonfinancial risk on intertemporal choice. Our purpose is to provide a simple framework that can be adopted in fields like representative-agent macroeconomics, corporate finance, or political economy, where most modelers have chosen not to incorporate serious nonfinancial risk because available methods were too complex to yield transparent insights. Our model produces an intuitive analytical formula for target assets, and we show how to analyze transition dynamics using a familiar Ramsey-style phase diagram. Despite its starkness, our model captures most of the key implications of nonfinancial risk for intertemporal choice.
urn:nbn:de:hebis:30-68339
Keywords: C61; D11; E24; 330; Risk; Uncertainty; Precautionary Saving; Buffer Stock Saving; Sparen; Kassenhaltungsansatz; Entscheidung bei Unsicherheit; Zeitpräferenz; Theorie